From the first to the third Critique: Non-conceptual content and the fate of the imagination - Sakızlı, Selda Salman (My University, 2020)
The faculty of imagination and its role in the Critique of the Power of Judgement are at the hearth of a very important controversy: Is aesthetic judgement conceptual? This is not a simple question to deal with since it is directly related with the cognitive claims in the Critique of Pure Reason. Different approaches, from analytic to continental traditions, from psychological readings of Kant to the advocates of philosophy of mind hold different views on this subject. This variety is a result of the status and the role of the imagination, and the kinds of syntheses it realizes which differs in the first and the second editions of the Critique of Pure Reason. In the first edition, imagination is considered as one of the three fundamental faculties among sensibility and apperception, and it is the agent of the syntheses. However, in the second edition, imagination becomes a sub-faculty of the understanding and the syntheses are realized by the understanding. I claim that the A edition of the CPR is more accurate with the entire critical project. Although philosophers like Wilfrid Sellars,1 John McDowell2 and Hannah Ginsborg3 defend that non-conceptual content is not possible, I disagree with this view and see it as a result of taking the B edition, additionally, the debate concerning the third Critique is a repercussion of this. Moreover, these disputes are also related with holding the first and the third Critiques as having completely distinct contents which opens up another “battle field”. I claim that the first and the third Critiques are connected through the faculties, and Kant was very well aware of the fact that he utilizes the same faculties as he used to explain human cognition in the CPR. 1 See Wilfrid Sellars, “The role of imagination in Kant’s theory of experience”. University of Pittsburgh, Archives of Scientific Philosophy, Wilfrid S. Sellars Papers, Box 39, Folder, 11, 1978 2 See John McDowell, Mind and World, Harvard University Press, 1996 2 See Hannah Ginsborg, “Was Kant a Nonconceptualist?” ? Philos Stud. 137, 2008, pp.65-77 4 A99-100 5 See. A89-91 /B122-123, Bl45 6 Robert Hanna, Kant and the Foundations of Analytic Philosophy, Clarendon Press, Oxford, 2001, p.52 7 Immanuel Kant, Critique of the Power ofJudgement, Trans. Paul Guyer & Eric Matthews, Cambridge University Press, New York, 2007, 5:209 Concerning the conceptual and non-conceptual contents, the crucial point is the threefold synthesis, especially the synthesis of apprehension that aims directly empirical and pure intuitions4 in the first edition of the CPR, and which is revisited in the introduction of the third Critique. Kant stresses in several sentences that intuitions and thoughts are different and they cannot hold each other’s place.5 Since sensibility and understanding need to be separate in transcendental philosophy, there is the need to combine them with a third faculty which is the faculty of imagination. Although I am not in analytic tradition, I agree with Robert Hanna who takes the first edition of the Critique and indicates that imagination as the third faculty can both serve to the sensibility and the understanding6 by the threefold synthesis, and there is non-conceptual content in imagination’s relation to sensibility. As indicated above, the claim that there is non-conceptual content in the synthesis of imagination finds its supports in the third Critique. Besides the synthesis of apprehension, this claim becomes obvious in the free play between the imagination and the understanding that occurs without submitting to any concepts. Kant clearly indicates that the feeling of beautiful does not come from a concept nor it aims at one.7 And this is the reason why aesthetic feelings are always subjective, and thus we do not have any rules for aesthetic appreciation.